Importancia de la motivación en el proceso de enseñanza aprendizaje y su influencia en el rendimiento académico de los estudiantes del 8vo, 9no, y 10mo año de educación básica del colegio nocturno El Guabo del cantón El Guabo, año lectivo 2012-2013 - Loayza Rios, Silvana Marianela (2013)
The investigated subject met the standards established by the Technical University of Machala, going by applying each step of the research, it has developed a general explanation of the problem under study, where in the development of the conceptual framework contents that relate arise directly with the subject, which has been based the development of the hypothesis, the same that have been proven to apply research instruments such as the survey of students and interviews with teachers in the intervention school of the canton El Guabo.